Effects of herbal medicine components on the physical properties of trial denture adhesives - Kenichiro Nakai; Takeshi Maeda; Guang Hong; Tadafumi Kurogi; Joji Okazaki (Dental Journal (Majalah Kedokteran Gigi), 2017)
Background: Denture adhesive is widely used in elderly people who wear complete dentures. Chinese herbal medicine has long been used for the treatment of oral disease. The addition of herbal medicine to denture adhesive might be used to develop an adhesive which is effective for xerostomia patients. Purpose: The purpose of this study was to evaluate physical properties and cytototoxicity of herbal medicine components in denture adhesive. Methods: This study used a combination of 35wt% PVM-MA, 20wt% CMC, 40wt% white petrolatum and 5wt% liquid paraffin as base materials. Three kinds of herbal medicine components: Maimendong (Ophiopogon), Fuling (Hoelen) and Dongkuizi (Cluster mallow seed) were added to base materials of 1wt%, 5wt% and 10wt%. The initial viscosity was measured using a controlled-stress rheometer (AR-G2). The adhesive strength was quantified according to ISO-10873 recommended procedures. All data was analyzed independently by one-way Anova combined with a Turkey’s multiple comparison test at a 5% level of significance. Results: Significant differences were observed between materials in initial viscosity (p < 0.05). Specifically, samples containing 5wt% and 10wt% of Maimendong (Ophiopogon) showed higher values compared with the control samples. The larger the amounts of herbal medicine components, the greater the changes in the adhesive strength of denture adhesives over time. The denture adhesives containing herbal medicine components do not have a cytotoxic effect and are safe for use in actual clinical practice. Conclusion: The study showed that the addition of herbal medicine components does not affect physical properties (i.e. initial viscosity and adhesive strength) of denture adhesive and cytotoxicity in fibroblast cells.